PENGEMBANGAN MODUL PEMBELAJARAN FISIKA BERBASIS KONTEKSTUAL PADA POKOK BAHASAN PEMANASAN GLOBAL UNTUK SISWA SMA - Nala Kurinta; Singgih Bektiarso; Maryani Maryani (JURNAL PEMBELAJARAN FISIKA, 2021)
The purpose of this research: 1) analyze the validity; 2) the effectivity of the contextual-based physics learning module on the subject of global warming for high school students. This research is research and development (R&D). The development model used refers to the Nieeven (2006) model which includes 3 stages, namely 1) preliminary research, 2) prototyping stage, 3) assessment stage. Data collection techniques used are interviews and literature study. The data analysis used is expert validation and practicality data analysis. Practical data analysis using quantitative descriptive. This data analysis technique is used to process the data obtained through a questionnaire in the form of a descriptive percentage. The percentage of data obtained from the lecturer's response questionnaire was calculated based on the Guttman scale. The results showed that: 1) expert validity was 3.77 with very valid criteria and with a reliability coefficient of 95%. While user validation shows very valid criteria with user validity results of 3.78 and with a reliability coefficient of 100%. Thus, this contextual-based physics module can be used as teaching material on global warming material. 2) The effectiveness of the calculated pretest and posttest results obtained an N-gain score of 0.79 which is included in the high category. So, the contextual-based physics learning module on the subject of global warming that was developed has effective criteria in improving student learning outcomes at SMAN 2 Jember, so it is suitable to be used as physics.